1993
DOI: 10.1212/wnl.43.6.1167
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis

Abstract: To clarify the role of cell-mediated versus humoral immune effector responses in myasthenia gravis (MG), we examined the occurrence of inflammatory cells in muscle from 30 patients with MG, determined the site of accumulation of the cells (at or remote from end-plates), enumerated and immunophenotyped those cells at the end-plate, and evaluated the frequency of deposition of the complement membrane attack complex (MAC) at the end-plate. Seven of 30 patients had well-defined collections of mononuclear cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(91 citation statements)
references
References 0 publications
3
86
0
2
Order By: Relevance
“…Pathology studies have demonstrated complement deposition in the motor endplate region in AChR MG [126][127][128]. In addition, the autoantibodies in AChR MG are predominantly IgG1 and IgG3, which are known to activate complement [129,130].…”
Section: Complement Inhibitionmentioning
confidence: 99%
“…Pathology studies have demonstrated complement deposition in the motor endplate region in AChR MG [126][127][128]. In addition, the autoantibodies in AChR MG are predominantly IgG1 and IgG3, which are known to activate complement [129,130].…”
Section: Complement Inhibitionmentioning
confidence: 99%
“…In MG and EAMG, major immune effectors of the disease process at the neuromuscular junctions are circulating IgG autoantibodies reactive to AChR, whereas the cellular inflammatory infiltrates in the muscles are sparse and not considered essential for the impaired neuromuscular transmission, both in humans and mice [16,19,20]. Therefore, we measured anti-murine AChR IgG (and related isotypes) in CCL2 -/-mice and control mice immunized Figure 1.…”
Section: B Cell and Autoantibody Responses In Ccl2 -/-Micementioning
confidence: 99%
“…In human MG, the strongest evidence for complement as a pathogenic mechanism derives from identification of antibody, C3 and MAC deposition at neuromuscular junctions from MG patients [5][6][7]. Depletion of serum complement components, C3 and C4 is observed in patients, but their levels are not related to severity of weakness [47].…”
Section: Complement Components and Their Roles In Mg And Eamgmentioning
confidence: 99%
“…In 1977, Engel appreciated the binding of complement components to the endplates of MG patients [5][6][7] and experimentally acquired MG (EAMG) animals [8]. Since then, the role of complement in the initiation, progression and susceptibility of the disease has been investigated as to the structural alterations of the neuromuscular junction and the systemic changes that occur to the immune system.…”
mentioning
confidence: 99%